The effect of sipatah-patah (Cissus quadrangularis Salisb) extract administration on osteoclast formation and osteoporosis treatment in female rats during post menopausal period - M. Sabri (Syiah Kuala University, 2011)
Cissus quadrangularis Linn (Cq) is a rambling shrub, characterized by a thick quadrangular fleshy stem and widely used to cope with joint pain, syphilis, venereal disease, and osteoporosis. This plant is containing calcium, phosphate and phyto-oestrogens. Hence the objective of the present study was to evaluate effect of the C. quadrangularis on bone recovery of rat. Blood was drawn once each 30 days to analyze serum calcium and phosphate concentration in blood. Rats were sacrificed to analyze bone histology. Os tibia fibula slice was stained with Hematoxylin Eosin (HE) method to observe osteoblast and osteoclast density, and Masson trichrome to observe trabeculae structure. ESP administration at longer period on treatment rats (OV-2) leads to more radiopaque bone mass than other groups including control group but osteoclast density is lower